Evaluation of the impact of management training in the province of Guantánamo (Research, Society and Development, 2022)
Business organizations are currently facing accelerated changes that occur in all areas of society; for this reason, the training of human resources - and especially those who direct - with a systemic approach, is an essential condition to upgrade their specialized managerial qualification. This presupposes that the valuation of training constitutes a resource to validate its constant improvement, and in this way to punctually distinguish the situation it presents, verifying the fulfillment of the objectives, results, effects and impacts. For these reasons, the objective of the research carried out was to develop a system of indicators to evaluate the impact of training for executives in Guantanamo’s Province, based on a Diploma in Business Management and Public Administration, which was evaluated with high impact once applied what was previously stated. This research constitutes a reference material for teachers, methodologists and managers because it offers instruments to evaluate the impact of training managers based on a system of indicators. The research methods used were: analytical-synthetic, inductive-deductive, historical-logical, statistical-mathematical, surveys, the study of documents, and the criteria of experts, which made it possible to evaluate the existing trends and approaches related to the subject matter study; as well as enriching, completing and contrasting information on the impact of the preparation received. It also made possible to assess the coherence and feasibility of the proposed indicators used in order to improve training as a process.